SURVEY ON THE PRACTICES ON CLIMATE CHANGE AWARENESS OF STUDENTTEACHERS OF UNIVERSITY OF EASTERN PHILIPPINES - CHERRY I. ULTRA, ANTONIETO L. ADORA, NELIA M. ADORA (International Journal of Modern Agriculture, 2021)
Climate change has broad adverse impacts. It affects not only our environment, but also economic and social development. Developing countries are generally warmer, more prone to rainfall variability, more dependent on agriculture – the most climate sensitive of economic sectors – as a result of low income have limited risk mitigation infrastructure. This study determined the climate change awareness and adaptation practices of students in the University of Eastern Philippines. The result showed that some elements of climate change are better understood than others. In a further indication of the lack of basic scientific knowledge which can help to build a more grounded and robust understanding of climate change, these future teachers struggle significantly with an understanding of the basic concepts of climate and weather. An indication of the confusion surrounding the concept of climate change adaptation, almost half of students correctly identified that climate is a term used to describe average weather over a prolonged period of time.